Pspice and Matlab for electronics : an integrated approach - Attia, John Okyere (Boca Raton : CRC Press, 2002)
Introduction to PSPICE; Matlab primer; Applications of PSPICE and MATLAB.
Includes bibliographical references and index.
Keywords: Integrated circuits; Integrated circuits, Very large scale integration -- Design and construction -- Data processing; PSpice; MATLAB; Electronic circuit design -- Data processing